Safety Stock Analysis: A Systematic Mapping Study - Amalia Saniy Soeprapti, Rizki; Arifianti, Ria; Muftiadi, Anang (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2023)
Safety Stock is a concept that emphasizes the importance of inventory owned by a company. Safety Stock addresses the inventory prepared by a company to prevent inventory shortages when market demand is unstable. Therefore, this article aims to classify, identify scientific publications, and conduct a thematic analysis of current literature to create an extensive and detailed understanding of the field of Safety Stock. The research method used by researchers is a Systematic Mapping Study (SMS) to examine scientific publications in the field of Safety Stock produced based on the focus and type of research over time. The results of this study resulted in the categorization and quantification of Safety Stock studies in various dimensions as well as an overview of current research topics and trends.